Legal Protection of Indigenous Knowledge Systems through IKS for Large-Scale Enterprises - Kethireddy, Rajashekhar Reddy (International Journal of Computing and Engineering, 2018)
The formation of the Association of Southeast Asian Nations (ASEAN) Economic Community (AEC) in 2015 has created new challenges for small and medium-sized businesses (SMEs) in Malaysia. These challenges are in addition to the consequences of globalization that have already been experienced by low-cost nations such as India and China. It is critical for small and medium-sized firms (SMEs) to keep their competitive edge because they are the backbone of the Malaysian economy. A business can increase its competitiveness by implementing the kaizen idea of continuous improvement. Challenges and opportunities for small and medium-sized firms to adopt kaizen are explored in this article. Several factors were found to play a role in the effective execution of Kaizen. Among these were an articulated business plan, effective management of company information, employee agency, and two-way dialogue between upper and lower-level management. Another important factor was having a Kaizen champion on staff. However, environmental monitoring systems still do not have enough evidence to justify the semantic description of these many data sources. The compatibility issues can only be resolved with a tailored semantic middleware solution. Detailed herein is the design of a cross-domain middleware system capable of semantic integration and inference generation from a variety of data sources. Improved environmental monitoring systems are possible thanks to semantic technology's application to the prediction and forecasting of complicated environmental phenomena.